212k views
17 votes
Substitute this simultaneous linear equation

x - 4y = - 6 \\ 2x + 3y = 10


User Firephil
by
6.3k points

1 Answer

8 votes

Answer:


x - 4y = - 6 \: ......(1) \\ \\ 2x + 3y = 10 \: .......(2)

from equation (1)


x - 4y = - 6 \\ \\ 4y = x + 6 \\ \\ y = (x + 6)/(4)

Substitute " y " in equation (2)


2x + 3y = 10 \\ \\ 2x + 3( (x + 6)/(4) ) = 10 \\ \\ 2x +( (3x + 18)/(4) ) = 10 \\ \\ \\ (8x + 3x + 18)/(4) = 10 \\ \\ \\ 8x + 3x + 18 = 10 * 4 \\ \\ 11x + 18 = 40 \\ \\ 11x = 40 - 18 \\ 11x = 22 \\ \\ x = (22)/(11) \\ \\ x = 2


y = (x + 6)/(4) \\ \\ y = (2 + 6)/(4) \\ \\ y = (8)/(4) \\ \\ y = 2

User Jahron
by
6.1k points